Analysis of Corporate Governance and Relative Efficiency of Public Companies Listed in Indonesian Stock Exchange - Olivia Liputri; Junius Tirok (Bina Nusantara University, 2009)
This research aims to investigate the relationship between corporate governance and company’s relative efficiency. The research sample is 34 public companies listed in Indonesian Stock Exchange. A modified Jones (1991) model is used to detect the earnings management practice as a proxy to corporate governance. In regard with the efficiency score, this research employs Data Envelopment Analysis (DEA). This research find that the there is no significant relationship between corporate governance and its efficiency.